P4.63 Designing human immunodeficiency virus counselling and testing services to maximise uptake among high school learners in south africa: what matters?. (8th July 2017) - Strauss, Michael; George, Gavin; Rhodes, Bruce
Abstract : Introduction: Increasing human immunodeficiency virus (HIV) testing in South Africa is vital for the HIV response. Targeting young people is important as they become sexually active and because HIV risk rapidly increases as youth enter their 20s. This study aims to increase the understanding of high school learners' preferences regarding the characteristics of HIV testing service delivery models and to inform policy makers and implementers regarding potential barriers to and facilitators of HIV testing. Methods: An attitudinal survey was used to examine HIV testing prefer- ences among 248 high school learners in KwaZulu-Natal. Statistical tests were used to identify the most favoured characteristics of testing service delivery models and examine key differences in preferences based on demographic characteristics and testing history. Results: Most learners were found to prefer testing offered at a clinic on a Saturday (43%), using a finger prick test (59%), conducted by a doctor (61%) who also provides individual counselling (60%). Shorter testing times were preferred, as well as a monetary incentive to cover any associ- ated expenses. Time, location, the type of test, and who conducts the test were most important. However, stratified analysis suggests that preferences diverge, particularly around gender, grade, but also sexual history and previous testing experience. Conclusion: Human immunodeficiency virus testing services can be improved in line with preferences, but there is no single optimal design that caters to the preferences of all learners. It is unlikely that a "one-size-fits-all" approach will be effective to reach HIV testing targets. A range of options may be required to maximise coverage.